Exploring Sustainable Value Propositions in Logistics Services – How Digitalization and Data Support Greener Services - Khan, Fuad; Eriksson, Taina; Heikkilä, Marikka; Ertiö, Titiana (Slovenia, 2025)
Employing a multiple-case study method, this study examines the value propositions in sustainable logistics services. We explored publicly accessible data on the financial, functional, and emotional aspects of the value propositions offered by four companies. We first discovered that digitalization plays a crucial role in value proposition creation supporting low emission logistics ecosystems. Specifically, digital solutions promise cost reduction opportunities across the entire value chain as financial value proposition; route optimization and regulatory compliance as functional value propositions; and transparency, trust, and credibility as emotional value propositions. Second, the reduction of fossil fuels as a functional value proposition is identified as a target for all companies. Third, functional value propositions prelude emotional value propositions, i.e. through sustainability certificates, service providers establish transparency, ensure value chain compliance, and ultimately build trust among customers. By highlighting the differences and similarities in value propositions, this study explores sustainable business model innovation and offers critical perspectives for organizations aiming to shift towards sustainable logistic service provision.
37th Bled eConference – Resilience Through Digital Innovation: Enabling the Twin Transition: June 9 – 12, 2024, Bled, Slovenia, Conference Proceedings